Effect of Previous Standing-up Exercise on Forward Bending Test in the Elderly - Morozumi, Kazunori; Nishiya, Takuya; Takeuchi, Yoshie; Yasuda, Akimasa; Fujiwara, Takayuki; Yamamoto, Iwao; Karasuno, Hiroshi (Journal of Physical Therapy Science, 2003)
In this study, we tested the effect of a standing-up exercise on forward bending in the long sitting position in elderly subjects. We compared the subjects' abilities to perform forward bending under two conditions: after standing-up exercise and without the standing-up exercise. The objective of this study was to propose, strategies for instructing the elderly in health exercise and low back pain prevention exercise. The results indicated that forward bending in the long sitting position measured after the standing-up exercise improved significantly (p<0.001) compared with those without performing the standing-up exercise. We hypothesized that contraction of muscles surrounding the hip joints and knee joints during the standing-up exercise acted as a light load exercise and provided some inhibitory effects on hamstring muscles and back muscles and lumbar regions. The possible inhibitory effects that could have occurred include: i) reciprocal inhibition against antagonistic muscles, ii) relaxation of the hip joint extensors after the maximal contraction, and iii) improvement of the preparatory state for the subsequent exercise brought about by accelerated peripheral blood circulation and temperature rise in the muscles. We report here on the usefulness of muscle contraction, for example, by standing-up before instructing the elderly in health exercise and low back pain prevention exercise, in that it makes the subsequent stretching exercise more effective. We also suggest the necessity of the order of exercises to be practiced in physical treatment.